(untitled) (Ameghiniana, 2014)
Diatom assemblages from a core at the north of Mar Chiquita coastal plain were analyzed in order to identify environmental changes due to salinity and depth. The core contains sediments dated at the base in 5802±70 C years BP. Four lithological units were defined: greenish-grey silt, brownish-grey sandy silt, heterolithic facies and brown sandy silt. Two hundred diatom species were identified and grouped based on their salinity tolerances and life form. Cluster analysis defined two diatom zones. The lower section of the sedimentary sequence (from the base to 90 cm depth, Zone I) was dominated by Paralia sulcata (Ehrenberg) Cleve and Psammococconeis cf. disculoides (Hustedt) García accompanied by marine-brackish plankton, epipsammon and epiphytes indicating coastal marine conditions. From 90 cm towards the top (Zone II), salinity and depth decrease: P. sulcata decline and appear Planothidium delicatulum (Kützing) Round and Bukht (brackish) and Hippodonta hungarica Grunow (brackish freshwater taxa), benthic and epiphytes diatoms increased. Multidimensional Scaling Analysis (MDS) showed that fossil diatom assemblages were similar to the modern assemblages from the inlet of Mar Chiquita coastal lagoon. These new diatom and sedimentological data support the regional model for the Holocene sea-level fluctuation and allow inferring the existence of a marginal coastal system during the regressive phase that evolved into a brackish-freshwater coastal lagoon and marsh.